Anode electrode sheet, electrochemical device, and electronic device
Patent Information
- Application Number
- CN202522091201.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2035-09-28
AI Technical Summary
受限于硅材料本身导电性的问题,使得电池的充电窗口受限
[0020]为使本申请实施例的目的、技术方案和优点更加清楚,下面将对本申请实施例中的技术方案进行清楚、完整地描述,显然,所描述的实施例是本申请一部分实施例,而不是全部的实施例。基于本申请中的实施例,本领域普通技术人员在没有做出创造性劳动前提下所获得的所有其他实施例,都属于本申请保护的范围。本申请的实施例可能会有省略不必要的详细说明的情况。例如,有省略对已众所周知的事项的详细说明、实际相同结构的重复说明的情况。这是为了避免以下的说明不必要地变得冗长,便于本领域技术人员的理解。
Smart Images

Figure CN224907985U_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical device technology, specifically to anode plates, electrochemical devices, and electronic equipment. Background Technology
[0002] As the consumer market develops, the demands on lithium-ion battery capacity are becoming increasingly stringent, leading to a shift in the active material layer of the anode electrode from a pure graphite system to a silicon-doped system. However, the inherent conductivity of silicon limits the battery's charging window.
[0003] Therefore, it is urgent to improve the structure of the anode electrode to increase the charging window of the cell while ensuring the cell capacity. Utility Model Content
[0004] The purpose of this application is to overcome the shortcomings of the prior art and provide an anode electrode, an electrochemical device, and an electronic device. This application sequentially deposits a first anode active material layer, a conductive layer, and a second anode active material layer on at least one side surface of the anode current collector, which can effectively improve the conductivity of the anode electrode and increase the charging window and capacity of the battery cell. By setting a first crack structure in the first anode active material layer, this application can improve the adhesion between the first anode active material layer and the conductive layer, preventing material separation. By setting a second crack structure in the second anode active material layer, it can effectively increase the contact area between the anode electrode and the electrolyte, thereby increasing the electrolyte retention capacity of the anode electrode and effectively improving the charging window of the battery cell.
[0005] To achieve the above objectives, in a first aspect of this application, an anode electrode is provided, comprising an anode current collector and a first anode active material layer, a conductive layer, and a second anode active material layer sequentially disposed on at least one side surface of the anode current collector, wherein the first anode active material layer has a first crack structure and the second anode active material layer has a second crack structure.
[0006] The thickness of the first anode active material layer is h1, and the depth of the first crack structure is d1; the thickness of the second anode active material layer is h2, and the depth of the second crack structure is d2; the anode electrode satisfies: 0 < d1 / (h1+h2) ≤ 0.2, and / or, 0 < d2 / (h1+h2) ≤ 0.2.
[0007] Preferably, the anode electrode satisfies: 0.1≤d1 / (h1+h2)≤0.2, and / or, 0.1≤d2 / (h1+h2)≤0.2.
[0008] Preferably, 1≤h1 / h2≤3.
[0009] Preferably, the crack width of the first crack structure is 70–90 μm, the crack length is 3–10 μm, and the crack distribution density is 10–30 cracks / 1540.2 mm. 2 .
[0010] Preferably, the crack width of the second crack structure is 60–100 μm, the crack length is 3–10 μm, and the crack distribution density is 15–35 cracks / 1540.2 mm. 2 .
[0011] Preferably, the first crack structure includes at least one of linear cracks, network cracks, and radial cracks.
[0012] Preferably, the second crack structure includes at least one of linear cracks, network cracks, and radial cracks.
[0013] Preferably, the thickness h3 of the conductive layer is 0.3≤h3 / (h1+h2)≤0.1.
[0014] Preferably, the thickness of the conductive layer is 1–5 μm.
[0015] In a second aspect of this application, an electrochemical device is provided, including the anode electrode provided in the first aspect of this application.
[0016] Preferably, the electrochemical device further includes a cathode electrode and a diaphragm, wherein the diaphragm is disposed between the anode electrode and the cathode electrode.
[0017] In a third aspect of this application, an electronic device is provided, including the electrochemical device provided in the second aspect of this application. Attached Figure Description
[0018] Figure 1 A cross-sectional view of the anode electrode provided in this application.
[0019] In the figure, 1-anode current collector, 2-first anode active material layer, 3-conductive layer, 4-second anode active material layer, 5-first crack structure, 6-second crack structure. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. The embodiments of this application may omit unnecessary detailed descriptions. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art.
[0021] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0022] As used herein, the terms “approximately,” “generally,” “substantially,” and “about” are used to describe and indicate small variations. When used in conjunction with an event or situation, the terms may refer to examples in which the event or situation occurred precisely and examples in which the event or situation occurred very approximately. For example, when used in conjunction with numerical values, the terms may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. For example, if the difference between two values is less than or equal to ±10% of the average of the values (e.g., less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%), then the two values can be considered "substantially" the same.
[0023] Furthermore, for ease of description, "first," "second," "third," etc., can be used in this article to distinguish different components of a figure or a series of figures. "First," "second," "third," etc., are not intended to describe the corresponding components.
[0024] Additionally, quantities, ratios, and other numerical values are sometimes presented in range format in this document. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only the numerical values explicitly specified as range limits, but also all individual numerical values or subranges covered within the range, as if each numerical value and subrange were explicitly specified.
[0025] In the detailed description and claims, a list of items connected by the terms "one of," "among," "a kind of," or other similar terms may mean any of the listed items. For example, if items A and B are listed, then the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, then the phrase "one of A, B, and C" means only A; only B; or only C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0026] In the detailed description and claims, the list of items connected by the term "at least one of" can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.
[0027] In the following description, all figures disclosed in this application are approximate values, regardless of whether the terms "about" or "approximately" are used in conjunction. They may vary by 1%, 2%, 5%, or sometimes 10% to 20%. Whenever a range of values with a lower limit (RL) and an upper limit (RU) is disclosed, any values falling within that range are specifically disclosed. Specifically, the following values within this range are specifically disclosed: R = RL + k * (RU - RL), where k is a variable with a 1% increment from 1% to 100%, that is, k is 1%, 2%, 3%, 4%, 5%, ..., 50%, 51%, 52%, ..., 95%, 96%, 97%, 98%, 99%, or 100%. Furthermore, any range of values defined by the two R values as defined above are also specifically disclosed.
[0028] Throughout this specification, references to "implementation," "partial implementation," "one implementation," "another implementation," "specific method," or "partial method" mean that at least one implementation or embodiment in this application includes the specific features, structures, materials, or characteristics described in that implementation or embodiment.
[0029] In this application, numerical ranges are involved. Unless otherwise specified, the numerical ranges mentioned above are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form a range not explicitly stated.
[0030] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the invention, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the invention.
[0031] To achieve the above objectives, please refer to Figure 1 In a first aspect of this application, an anode electrode is provided, comprising an anode current collector 1, and a first anode active material layer 2, a conductive layer 3, and a second anode active material layer 4 sequentially disposed on at least one side surface of the anode current collector 1. The first anode active material layer 2 has a first crack structure 5, and the second anode active material layer 4 has a second crack structure 6.
[0032] The thickness of the first anode active material layer 2 is h1, and the depth of the first crack structure 5 is d1; the thickness of the second anode active material layer 4 is h2, and the depth of the second crack structure 6 is d2; the anode electrode satisfies: 0 < d1 / (h1+h2) ≤ 0.2, and / or, 0 < d2 / (h1+h2) ≤ 0.2.
[0033] This application sequentially provides a first anode active material layer 2, a conductive layer 3, and a second anode active material layer 4 on at least one side surface of the anode current collector 1, which can effectively improve the conductivity of the anode electrode and enhance the charging window and capacity of the battery cell. By providing a first crack structure 5 in the first anode active material layer 3, this application can improve the adhesion between the first anode active material layer 2 and the conductive layer 3, preventing material separation. By providing a second crack structure 6 in the second anode active material layer 4, the contact area between the anode electrode and the electrolyte can be effectively increased, thereby increasing the electrolyte retention of the anode electrode and effectively enhancing the charging window of the battery cell.
[0034] In some embodiments, the anode electrode satisfies: 0.1≤d1 / (h1+h2)≤0.2, and / or, 0.1≤d2 / (h1+h2)≤0.2.
[0035] The inventors discovered through research that when the anode electrode satisfies 0.1≤d1 / (h1+h2)≤0.2 and 0.1≤d2 / (h1+h2)≤0.2, the overall performance of the battery cell is better.
[0036] For example, d1 / (h1+h2) can be 0.1, 0.12, 0.13, 0.14, 0.15, 0.2, 0.22, 0.25, 0.28, 0.2, or a range consisting of any two sets of values.
[0037] For example, d2 / (h1+h2) can be 0.1, 0.12, 0.13, 0.14, 0.15, 0.2, 0.22, 0.25, 0.28, 0.2, or a range consisting of any two sets of values.
[0038] In some implementations, 1 ≤ h1 / h2 ≤ 3.
[0039] For example, h1 / h2 can be a range consisting of 1, 1.5, 2, 2.5, 3, or any two sets of values therein.
[0040] In some embodiments, the first crack structure 5 has a crack width of 70–90 μm, a crack length of 3–10 μm, and a crack distribution density of 10–30 cracks / 1540.2 mm. 2 .
[0041] In some embodiments, the second crack structure 6 has a crack width of 60–100 μm, a crack length of 3–10 μm, and a crack distribution density of 15–35 cracks / 1540.2 mm. 2 .
[0042] In some embodiments, the first crack structure 5 includes at least one of linear cracks, network cracks, and radial cracks.
[0043] In some embodiments, the second crack structure 6 includes at least one of linear cracks, network cracks, and radial cracks.
[0044] In some embodiments, the thickness h3 of the conductive layer 3 is 0.3≤h3 / (h1+h2)≤0.1.
[0045] In some embodiments, the thickness of the conductive layer 3 is 1–5 μm.
[0046] For example, the thickness of the conductive layer 3 can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any two of these values.
[0047] In this application, the thickness refers to, as in... Figure 1 The dimension along the Y-axis.
[0048] In some embodiments, the anode current collector 1 may be a copper foil.
[0049] In some embodiments, the first anodic active material layer 2 may include an anodic active material, and the second anodic active material layer 4 may include an anodic active material.
[0050] In some embodiments, the anolyte material in the first anolyte layer 2 includes at least one of carbon material and silicon material; the anolyte material in the second anolyte layer 2 includes at least one of carbon material and silicon material. The silicon material includes at least one of silicon, silicon suboxide, and silicon-carbon material; the carbon material includes at least one of natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, and soft carbon.
[0051] In some embodiments, the mass percentage of carbon in the first anode active material layer 2 is greater than the mass percentage of carbon in the second anode active material layer 4, and the mass percentage of silicon in the first anode active material layer 2 is less than the mass percentage of silicon in the second anode active material layer 4. If the first anode active material layer 2 and the second anode active material layer 4 meet the above conditions, most of the lithium insertion sites of the anode electrode can be concentrated in the second anode active material layer 4 (lithium insertion sites, silicon is more abundant than graphite), reducing the diffusion path of lithium ions and thus improving the charging window of the cell; it can also suppress lithium insertion expansion, thereby reducing the stretching of the foil and preventing breakage.
[0052] For example, the anodic active material in the first anodic active material layer 2 is a carbon material, and the anodic active material in the second anodic active material layer 4 is a silicon material.
[0053] In some embodiments, the first anodic active material layer 2 comprises the following components by mass percentage: 95-98% anodic active material, 0.5-1.5% conductive agent, 1-2.5% binder, and 0.5-1% dispersant.
[0054] In some embodiments, the second anodic active material layer 4 comprises the following components by mass percentage: 85-95% anodic active material, 2-4% conductive agent, 2-8% binder, and 1-3% dispersant.
[0055] In some embodiments, the conductive layer 3 may include the following components by mass percentage: 96-99% conductive agent and 1-4% binder.
[0056] In this application, the conductive agent may include at least one of acetylene black, Ketjen black, Super P, carbon nanotubes, conductive graphite, graphene, and conductive carbon fiber; the binder may include at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber, polyacrylonitrile, polyacrylic acid, polyvinyl alcohol, polyimide, and polyamide-imide; and the dispersant may include at least one of carboxymethyl cellulose, lithium carboxymethyl cellulose, and sodium carboxymethyl cellulose.
[0057] In this application, the first crack structure and the second crack structure can be formed by existing methods. This application does not have any particular restrictions on the formation method of the first crack structure and the second crack structure. The depth, width, length and distribution density of the first crack structure and the second crack structure can be controlled by adjusting process parameters such as the temperature of the coating oven, the air frequency of the coating oven, and the pressure of the roller during the anode electrode preparation process.
[0058] In a second aspect, this application provides an electrochemical device, including any device in which an electrochemical reaction occurs to interconvert chemical energy and electrical energy, specifically and non-limiting examples including all types of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. In particular, the electrochemical device is a lithium secondary battery, including lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.
[0059] The electrochemical device includes an anode, a cathode, an electrolyte, and a diaphragm. The diaphragm is located between the anode and the cathode, and the anode used in the electrochemical device is the anode described above in this application.
[0060] In some embodiments, the cathode electrode may include a cathode current collector, and at least one side surface of the cathode current collector is provided with a cathode active material layer.
[0061] In some embodiments, the cathode current collector is a metal foil, which may be an aluminum foil.
[0062] In some embodiments, the cathode active material layer may include the following components by mass percentage: 96-98% cathode active material, 1-2.5% conductive agent, and 0.5-1.5% binder.
[0063] The cathode active material may include at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, transition metal phosphate, and lithium iron phosphate.
[0064] In this application, the material of the diaphragm may include at least one of polypropylene, polyethylene, and nonwoven fabric.
[0065] In a third aspect of this application, an electronic device is provided, including the electrochemical device provided in the second aspect of this application.
[0066] The electronic device described in this application is not particularly limited and may be any electronic device known in the prior art.
[0067] The application of the electrochemical device of the present invention is not particularly limited, and it can be used in any electronic device known in the prior art. According to some embodiments of the present invention, the electronic device includes, but is not limited to, mobile phones, smartphones, laptops, tablets, wearable devices, smartwatches, smart bracelets, smart glasses, power banks, televisions, game consoles, game controllers, digital cameras, smart speakers, headphones, keyboards, mice, monitors, drones, audio equipment, home appliances, toys, power tools, automobiles, motorcycles, electric bicycles, bicycles, robots, robot dogs, industrial robots, android robots, etc.
[0068] The inventors conducted numerous research experiments during the research process, including designing and fabricating different secondary batteries and testing their performance. Some of the experimental examples and test results are listed below to illustrate this application:
[0069] Example 1
[0070] This embodiment provides a secondary battery, which includes an anode electrode, a cathode electrode, and a separator. The structure of the anode electrode is as follows: Figure 1 As shown, the anode electrode includes an anode current collector 1, and a first anode active material layer 2, a conductive layer 3, and a second anode active material layer 4, which are sequentially stacked on two opposite surfaces of the anode current collector 1. The first anode active material layer 2 has a first crack structure 5, and the second anode active material layer 4 has a second crack structure 6. The thickness of the first anode active material layer 2 is h1, and the thickness of the second anode active material layer 4 is h2. The total thickness of one side of the current collector (i.e., h1+h2) is 50μm, and the ratio of h1 to h2 is 7:3. The thickness h3 of the conductive layer is shown in Table 1.
[0071] This embodiment provides a secondary battery, and the preparation method of the secondary battery is as follows:
[0072] S1. Preparation of the anode plate:
[0073] Artificial graphite, conductive agent single-walled carbon nanotubes, binder polyacrylic acid and dispersant carboxymethyl cellulose were dispersed in deionized water at a weight ratio of 98:0.5:1:0.5 to prepare slurry A, which was then sieved for later use.
[0074] Conductive single-walled carbon nanotubes and binder were dispersed in deionized water at a weight ratio of 98:2 to prepare slurry B, which was then sieved for later use.
[0075] Silicon material (Si), conductive agent (conductive carbon black), binder styrene-butadiene rubber and dispersant carboxymethyl cellulose were dispersed in deionized water at a weight ratio of 95:2:2:1 to prepare slurry C, which was then sieved for later use.
[0076] Slurry A, slurry B, and slurry C are sequentially and uniformly coated onto a copper foil current collector to obtain a first anode active material coating, a conductive coating, and a second anode active material coating, which are then coated on both sides. When coating slurry A and slurry C, the depth, width, length, and distribution density of the crack structure are controlled by adjusting the temperature and air frequency of the coating oven. Then, the anode electrode is obtained by drying, winding, rolling, and die-cutting.
[0077] S2. Preparation of the cathode electrode:
[0078] The positive electrode active material LiCoO2, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in N-methylpyrrolidone solvent (NMP) at a mass ratio of 97:2:1 to obtain a positive electrode slurry with a solid content of 70%. The positive electrode slurry was coated on a current collector aluminum foil, dried at 85°C, cold-pressed, then trimmed and slit, and dried under vacuum at 85°C for 6 hours. The tabs were then welded to obtain the cathode electrode.
[0079] S3. Preparation of the diaphragm:
[0080] Choose a PP / PE / PP composite membrane (Celgard 2325).
[0081] S4. Preparation of electrolyte:
[0082] Lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent of dimethyl carbonate (DMC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC) (mass ratio of DMC, EC, and EMC was 3:5:2) to obtain the electrolyte.
[0083] S5. Preparation of secondary batteries:
[0084] The prepared cathode electrode, separator, and anode electrode are stacked in sequence, with the separator positioned between the cathode and anode electrodes, and then wound to obtain the battery cell. The battery cell is placed in an aluminum-plastic film outer packaging for sealing, and then baked in an 85°C vacuum oven for 48 hours. Electrolyte is injected into the dried battery cell, followed by sealing, settling, formation, shaping, and capacity testing, and then a second sealing to obtain the secondary battery.
[0085] Examples 2-5 and Comparative Example 1
[0086] The difference between Examples 2-5 and Comparative Example 1 and Example 1 is that, in Examples 2-5 and Comparative Example 1, the parameters (depth, width, length, distribution density) of the first crack structure and the second crack structure are changed by adjusting the temperature and air frequency of the coating oven when coating slurry A and slurry C, as shown in Table 1 below.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 1 is that this comparative example does not have a conductive layer.
[0089] Performance testing
[0090] (1) In step S1 of the above embodiments and comparative examples, the coated electrode sheet is directly taken, and the depth and width of all cracks in the selected area are measured by line spectroscopy, and the average value is taken.
[0091] CCD was used to measure the length and distribution density of the crack structure. Three regions were selected for measurement, each with an area of 1540.2 mm². 2 Measure the length of each crack and the number of cracks in each region, and take the average value;
[0092] Let the depth of the first crack structure 5 be d1 and the depth of the second crack structure 6 be d2, and calculate d1 / (h1+h2) and d1 / (h1+h2).
[0093] (2) Liquid retention coefficient: In the secondary battery preparation process of the above embodiments and comparative examples, the cell weight was weighed before the electrolyte injection step and after the second sealing step, respectively. The liquid retention amount was calculated by the following formula: Liquid retention amount = cell weight after second sealing + air bag weight - cell weight before electrolyte injection; The battery was placed in an environment of 25°C and charged at a constant current of 0.5C to the upper limit voltage of 4.5V. After reaching the upper limit voltage, it was switched to constant voltage charging until the current decayed to the cutoff current of 0.05C; After charging was completed, it was left to stand and discharged at a constant current of 0.2C to the lower limit voltage of 3.0V. The capacity released during discharge was recorded, which is the 0.2C first discharge capacity; The liquid retention coefficient was calculated according to the following formula: Liquid retention coefficient = Liquid retention amount / 0.2C first discharge capacity × 100%.
[0094] (3) Charging window: Repeatedly charge and discharge the battery. First, place the battery in an environment of 25°C for charging at a constant current of 0.5C to the upper limit voltage of 4.5V. After reaching the upper limit voltage, switch to constant voltage charging until the current decays to the cutoff current of 0.05C. After charging is completed, let it stand and discharge at a constant current of 0.2C to the lower limit voltage of 3.0V, and then let it stand for 1 minute.
[0095] After three charge-discharge cycles, the capacity released during the final discharge is the rated capacity of the battery cell; then, eight sets of charge-discharge cycles are performed sequentially using the following method:
[0096] ① In constant current constant voltage (CC-CV) mode, charge to the upper limit voltage of 4.5V according to the set rate, and then maintain the voltage until the current drops to the cutoff current of 0.05C.
[0097] ② Let stand for 5 minutes;
[0098] ③ Discharge at a constant current at a fixed discharge rate (e.g., 0.2C) until the cutoff voltage (e.g., 3.0V);
[0099] ④ Let stand for 5 minutes;
[0100] Repeat steps ① to ④ above 20 times, then change to the next charging rate for testing;
[0101] The charging rates in the eight charge-discharge cycles are 1.8C, 2.0C, 2.2C, 2.4C, 2.6C, 2.8C, 3.0C, 3.2C, and 3.4C, respectively.
[0102] Table 1
[0103]
[0104] In Table 1, " / " indicates that no corresponding structural layer has been set.
[0105] Table 2
[0106] Example 1 1.63g / mAh 1000mAh 2.8C Example 2 1.46g / mAh 1005mAh 2.6C Example 3 1.70g / mAh 995mAh 2.8C Example 4 1.64g / mAh 1008mAh 2.2C Example 5 1.65g / mAh 972mAh 3.2C Comparative Example 1 1.85g / mAh 941mAh 3.4C Comparative Example 2 1.64g / mAh 1011mAh 1.8C
[0107] As can be seen from Examples 1-5, this application, by sequentially depositing a first anode active material layer, a conductive layer, and a second anode active material layer on at least one side surface of the anode current collector, and adjusting the thickness h1 of the first anode active material layer, the depth d1 of the first crack structure, the thickness h2 of the second anode active material layer, and the depth d2 of the second crack structure, ensures that the anode electrode satisfies: 0 < d1 / (h1+h2) ≤ 0.2, 0 < d2 / (h1+h2) ≤ 0.2. This can increase the liquid retention of the anode electrode while effectively improving the cell capacity and charging window, ensuring that the liquid retention coefficient of the anode electrode is not less than 1.46 × 10⁻⁶. 3 g / mAh, the cell capacity is not less than 995mAh, and the charging window is not less than 2.6C.
[0108] Compared with the embodiments, in Comparative Example 1, d1 / (h1+h2) and d2 / (h1+h2) are too large. Although the liquid retention coefficient and charging window of the anode electrode are high, the capacity of the cell is significantly reduced.
[0109] Compared to the embodiments, Comparative Example 2 did not have a conductive layer, which resulted in a significant decrease in the charging window of the battery cell.
[0110] The embodiments of this application have been described in detail above with reference to the accompanying drawings. However, this application is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of this application. Furthermore, unless otherwise specified, the embodiments and features described in the embodiments of this application can be combined with each other.
Claims
1. An anode electrode, characterized in that, The anode current collector includes a first anode active material layer, a conductive layer, and a second anode active material layer sequentially disposed on at least one side surface of the anode current collector. The first anode active material layer has a first crack structure, and the second anode active material layer has a second crack structure. The thickness of the first anode active material layer is h1, and the depth of the first crack structure is d1; the thickness of the second anode active material layer is h2, and the depth of the second crack structure is d2; the anode electrode satisfies: 0 < d1 / (h1+h2) ≤ 0.2, and / or, 0 < d2 / (h1+h2) ≤ 0.
2.
2. The anode plate as described in claim 1, characterized in that, The anode electrode satisfies: 0.1≤d1 / (h1+h2)≤0.2, and / or, 0.1≤d2 / (h1+h2)≤0.
2.
3. The anode plate as described in claim 1, characterized in that, 1≤h1 / h2≤3.
4. The anode plate as described in claim 1, characterized in that, The first crack structure has a crack width of 70–90 μm, a crack length of 3–10 μm, and a crack distribution density of 10–30 cracks per 1540.2 mm. 2 ; And / or, the crack width of the second crack structure is 60–100 μm, the crack length is 3–10 μm, and the crack distribution density is 15–35 cracks / 1540.2 mm. 2 .
5. The anode plate as described in claim 1, characterized in that, The first crack structure includes at least one of linear cracks, network cracks, and radial cracks; And / or, the second crack structure includes at least one of linear cracks, network cracks, and radial cracks.
6. The anode plate as described in claim 1, characterized in that, The thickness h3 of the conductive layer is 0.3≤h3 / (h1+h2)≤0.
1.
7. The anode plate as described in claim 1, characterized in that, The thickness of the conductive layer is 1–5 μm.
8. An electrochemical device, characterized in that, Includes the anode electrode sheet as described in any one of claims 1 to 7.
9. The electrochemical device as described in claim 8, characterized in that, It also includes a cathode electrode and a diaphragm, wherein the diaphragm is disposed between the anode electrode and the cathode electrode.
10. An electronic device, characterized in that, The electrochemical device includes any one of claims 8 to 9.